2015
DOI: 10.1186/s12866-015-0553-y
|View full text |Cite
|
Sign up to set email alerts
|

Multiple antibiotic resistances among Shiga toxin producing Escherichia coli O157 in feces of dairy cattle farms in Eastern Cape of South Africa

Abstract: BackgroundShiga toxin–producing Escherichia coli (STEC) O157:H7 is a well-recognized cause of bloody diarrhea and hemolytic-uremic syndrome (HUS). The ability of STEC strains to cause human disease is due to the production of Shiga toxins. The objectives of this study were to determinate the prevalence, serotypes, antibiotic susceptibility patterns and the genetic capability for Shiga toxin production in Escherichia coli (STEC) strains isolated from dairy cattle farms in two rural communities in the Eastern Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
81
3
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(103 citation statements)
references
References 39 publications
17
81
3
2
Order By: Relevance
“…Genetic profiling of the strA gene revealed that 50.88 % of the isolates harboured the resistance gene. The findings in this study are very similar to those of our previous study on virulence and antimicrobial resistance profiles of enterococcal isolates from pig farms within the same study area (Iweriebor et al, 2015b). Diarra et al (2010) also reported the prevalence of high antimicrobial resistance among enterococcal isolates from broiler chickens in Canada.…”
Section: Acquired Resistance To Vancomycin Is Mediated By Various Gensupporting
confidence: 81%
See 3 more Smart Citations
“…Genetic profiling of the strA gene revealed that 50.88 % of the isolates harboured the resistance gene. The findings in this study are very similar to those of our previous study on virulence and antimicrobial resistance profiles of enterococcal isolates from pig farms within the same study area (Iweriebor et al, 2015b). Diarra et al (2010) also reported the prevalence of high antimicrobial resistance among enterococcal isolates from broiler chickens in Canada.…”
Section: Acquired Resistance To Vancomycin Is Mediated By Various Gensupporting
confidence: 81%
“…Antibiotic-resistant Enterococcus isolates from animal production have been reported (Aslam et al, 2012;Iweriebor et al, 2015a, b;Iwu et al, 2015; Jackson et al, 2007;Simjee et al, 2006). The resistance levels observed among our enterococcal isolates were higher than those reported in a Slovakian study on 82 isolates (Brtkova & Bujdakova, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One such E. coli pathotype which has been reported in milk outbreaks is the STEC which is a causative agent of haemorrhagic colitis and haemolytic uremic syndrome (HUS) (Oliver et al, 2009). The main route of infection with STEC in humans is via consumption of contaminated foods including milk, which is commonly associated with asymptomatic dairy cattle reservoirs (Iweriebor et al, 2015). Important STEC virulence encoding genes, which make E. coli an insidious threat to food safety, are the phage-encoded shigatoxin genes (stx1 and stx2) which inhibit protein synthesis of host cells and leads to cell death and intimin (eae) which mediate colonization.…”
Section: Introductionmentioning
confidence: 99%